Particularities of Legal Regulation and Harmonization of Proprietary Rights Legislation in the RSA, Brazil and China - DUDIN, Mihail Nikolaevich; FROLOVA, Evgenia Evgenevna; BELIKOVA, Ksenia Michailovna; BADAEVA, Natalia Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
In all countries under consideration, legal regulation of proprietary relationships is a reflection of the current level of social and economic development of these states, as well as of the objective necessity of including certain proprietary legal institutions into the system of rights for things: • the process of civil legislation reformation in Brazil and China, in so far as it relates to the institutions of the right of ownership and limited proprietary rights, is acceptable to be admitted as generally successful and meeting the stated objectives. The proprietary legislation of the Republic of South Africa is marked by high stability; • in spite of being based on Roman-Dutch proprietary rights legal institutions, the law of South Africa receives the required development due to the judges’ interpretative activity in the process of creating case laws. Such situation is determined by the fact that during the period of English rule the Republic of South Africa adopted the type of judicial system organization and activity common for the common law countries; • the improvement of legal systems, as well as the unification and harmonization of national legislations of China, Brazil and the Republic of South Africa, ensures the creation of a unified approach to social and political, and legal interaction, which ensures compliance with the private law and proprietary rights as the basic rights of democratic societies oriented to sustainable social and economic development.
Keywords: Proprietary Law, Private Law, Civil Law, domestic legislation, Brazil, China, the RSA